Transformasi Pendidikan Agama Islam di Politeknik: Integrasi Enam Sistem Nilai dalam Kerangka Teo-Etikal - Waway Qodratulloh S (Universitas Negeri Padang, 2025)
This study examines the integration of six theo-ethical values—spiritual, ethical, logical, teleological, aesthetic, and physiological—into Islamic Religious Education (PAI) learning at Politeknik Negeri Bandung. Employing a qualitative descriptive approach, data were collected through observations, interviews, and document analysis. The findings indicate that although all six values are present in the teaching materials and instructional practices, their presentation remains largely fragmented. The theological and ethical dimensions appear most prominent, whereas aesthetic and physiological aspects are underrepresented. The study advocates for a more integrative and contextualized approach to bridge spiritual idealism with the realities of vocational education. Such integration positions PAI as a transformative framework for holistic character development. The article recommends the development of a learning model that thematically embeds these values to equip students with integrity, life orientation, and professional readiness.